História da psicologia e psicologia histórica: seus critérios e suas diferenças - Filippo, Anna Cristina de (1984)
This paper (dissertation) makes a distinction between the historical psychology and the history of psychology in an attempt to show that the history of psychology deals with the study of the evolution of a science, therefore operating on conceptual levels. Aiming at a more comprehensive understanding of its object of study the: man -the concepts related to the physiological and psychological rules have been considered of high importance. These concepts are originated from the movement not only related to the natural sciences -physiological concepts, mainly tose about the reflexactions and the localization of the cerebral functions, biological concepts like those of the evolution and adaptability, interest in research, the outcoming of laboratories and atomistic approach to psychism but also related to philosophy-empiricism, associationism and scientific materialism. Fundamentaly, the history of psychology deals with the remain principle, or else, with the principle that supports the permanence of the human constitution during the History. On the other hand, psychologists, influenced by studies in the areas of sociology and anthropology, started to review their concepts, which brought into light a new view of the man, that is, a new understanding of the man, seen as a human being whose reality is essentially historical and whose behaviour not only causes changes in the social environment where he lives but also reflects them. This new view of the man is the landmark of the beginnings of the historical psychology which operates on factual levels instead of conceptual ones. The historical psychology deals not with a human constitution essencially steady, but with a humanbeing that changes during the History showing new caracteristics and new ways of conduct.